PELESTARIAN DAN PENGEMBANGAN WAYANG GEDOG - Sunardi Sunardi; Bambang Suwarno; Bagong Pujiono (Institut Seni Indonesia Surakarta, 2013)
Wayang gedog categorized as rare puppet that has uniqueness in the play genre, the puppets’forms, gending, sulukan, or form of the show. Wayang gedog had experienced glorious days inSurakarta Paku Buwana X Era, but today has suffered a setback. This is caused by the difficultyin dalang’s generation knowledge transfer; performance techniques is perceived difficult for newdalangs, the lack of public interest and the lack of administration elite’s support in developingwayang gedog. The attempts to revive can be done by revitalize the wayang gedog. How are takenby holding the conservation and development gedog puppet. The preservation and developmentof wayang gedog can be done by documenting the design and the show, as well as constructingwayang gedog’s performance development models.